Tourism consumers’ perceptions, attitudes and low-carbon tourism behaviors towards “dual carbon” of China - Lan Zhan; Jiening Yang; Mingshui Lin; Xinhua Qi (Frontiers in Environmental Science)
To support China’s “dual carbon” goals, understanding the drivers of low-carbon tourism behavior is crucial. This study investigates these drivers among tourists in Fujian Province, a region with significant ecological and economic diversity. Based on a survey of 1,064 tourists and employing a multiple linear regression model, we analyze how regional differences mediate the influence of cognition and attitudes on sustainable behavior. The research reveals a complex interplay of factors, with key findings indicating that:(i) There is significant regional heterogeneity in tourist perceptions and concerns. For instance, tourists in the economically advanced eastern region display high policy awareness but also attribute primary responsibility to the government and businesses. In contrast, those in the developing western region demonstrate a stronger personal willingness to change their consumption habits, while tourists in the south and north express concerns over potential impacts on travel comfort and costs. (ii) Higher policy awareness does not uniformly translate to positive behavior. Counter-intuitively, in eastern Fujian, greater awareness of “dual carbon” policies was found to negatively impact low-carbon consumption. This suggests that without addressing associated concerns about cost and convenience, mere awareness can create resistance rather than encourage participation. (iii) Pro-environmental attitudes are a more consistent and powerful driver of behavior than cognitive understanding alone. Across the province, a firm belief in the necessity of low-carbon tourism and its importance to the industry’s sustainable development were the most significant predictors of sustainable practices. This highlights that fostering a sense of shared value is more effective than simply disseminating policy information. These outcomes provide valuable, region-specific insights for formulating targeted sustainable tourism policies in Fujian and other similarly diverse areas.